The SMEs Funding Decisions through the Islamic Equity Crowdfunding Platform - Herlitah, Herlitah; Huda, Nurul; Prijadi, Ruslan; Sobari, Nurdin; Fatwa, Nur (Faculty of Economics, Universitas Negeri Indonesia,Indonesia, 2023)
Islamic Equity Crowdfunding is currently an alternative sharia-based financing for SMEs. In Indonesia, the Islamic Equity Crowdfunding platform began to appear in 2021, and has been growing until now. The purpose of this study is to analyze the factors that influence the funding decision of SMEs in the Halal Food Industry through the Islamic Equity Crowdfunding platform. Data was collected from SMEs in Indonesia by surveying 200 respondents, namely businesses in halal food. In this study the data obtained will be analyzed using the partial least squares technique which refers to the theory of planned behavior. The results showed that the decision of SMEs in seeking funding through Islamic Equity Crowdfunding was influenced by Subjective Norms, Perceived Behavioral Control, Product Knowledge, and Religiosity, but Intention was not influenced by Attitude.